In Vitro Evaluation on Resistance of Phytopythium vexans (NG Isolate) Cultured from Sublethal Concentration against Several Fungicides - Santika, Islaminati Anna; Wibowo, Arif; Suryanti, Suryanti; Sumardiyono, Christanti; Widiastuti, Ani (Universitas Gadjah Mada, 2023)
Phytopythium vexans isolated from potatoes rhizospher in Ngablak, Magelang, Central Java was reported having a potency to cause potato tuber rot in in vitro test. Some fungicides had been intensively applied in this area to control potato late blight even using sublethal dose. This study investigated resistance response of the pathogen against several fungicides which were Mancozeb, Dimethomorph, mixture of Mancozeb and Mefenoxam, and mixture of Oxathiapiprolin and Famoxadone. The experiment was conducted to observe the sensitivity response of pathogen against those fungicide and the experiment repeated with one of the isolates which growth in sublethal concentration to observe the resistance response. Both experiment data was analyzed by Probit Analysis. On sentivity test, data showed that P. vexans were insensitive against Dimethomorph, but it was sensitive against Mancozeb, mixture of Mancozeb and Mefenoxam, as well as mixture of Oxathiapiprolin and Famoxadone. On Mancozeb treatment, mycelia were inhibited 100% at the sugested concentration. However, at the sublethal concentration the mycelial collony grew abnormally. Pathogen isolate from the sublethal concentration were used as material for the resistance response study. The effect of the sublethal application of Mancozeb to P. vexans caused resistance to Mancozeb itself and cross resistance against Dimetomorph and mixture of Oxathiapiprolin and Famoxadone. It was proven by higher value of predicted EC50 and EC95 on the second experiment compared to the predicted EC50 and EC95 from the first one. The resistant P. vexans isolate was able to produce sporangium and chlamydospore.